Apoptosis-mediated cytotoxic effect of Caralluma adscendens var. attenuata on colon (HT29) and Hepatic (HepG2) cancer cell lines - Mallela Vijaya Jyothi; Eranti Bhargav; Chilamakuru Naresh Babu; Kanala Somasekhar Reddy; Bhupalam Pradeep Kumar; Ravi Prasad Rao (Wolters Kluwer Medknow Publications, 2019)
Introduction: Caralluma adscendens var. attenuata (Wight) Grav. and Mayur., a member of Apocynaceae, is a perennial stem succulent plant with wide distribution in tropics and subtropics of the world. This plant is reported for the presence of steroids, flavonoids, saponins, triterpenes, and pregnane glycosides, and is known to have antidiabetic and antiulcerogenic properties. Materials and Methods: In this study, an attempt was made to identify antioxidant capacity and cytotoxic potential of n-hexane and aqueous methanolic extracts of total stem part of C. adscendens var. attenuata. Antioxidant activity was evaluated by total phenolic content assay, total flavonoid content assay, free radical scavenging activity, and reducing ability methods. Cytotoxic activity was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) assay and nuclear staining methods for colorectal cancer cell lines HT29 and liver cancer cell lines HepG2. Results: MTT assay method has proven that the IC50 value was 10 μg/mL for both extracts, whereas for cisplatin standard, it was 2 μg/mL. By nuclear staining, the apoptotic cells were identified as oval masses with dark cytoplasm and dense green nuclear chromatin fragments indicating the programmed cell death for both n-hexane and aqueous methanolic extracts at the same concentration (10μg/mL). Conclusion: However, aqueous methanolic extract showed prominent cytotoxic potential against both cancer cell lines.